2014
DOI: 10.1113/jphysiol.2014.278259
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of sodium channel neuronal isoform Nav1.1 to late sodium current in ventricular myocytes from failing hearts

Abstract: Key pointsr Late Na + current (I NaL ) contributes to action potential remodelling and Ca 2+ /Na + changes in heart failure.r The molecular identity of I NaL remains unclear. r The contributions of different Na + channel isoforms, apart from the cardiac isoform, remain unknown.r We discovered and characterized a substantial contribution of neuronal isoform Na v 1.1 to I NaL . r This new component is physiologically relevant to the control of action potential shape and duration, as well as to cell Ca 2+ dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…Apart from the cardiac sodium channel Na V 1.5, neuronal sodium channel isoforms (ie, Na V 1.1, Na V 1.3, and Na V 1.6) are also thought to populate the T tubules 29, 30, 31, 32. Studies on expression and function of neuronal sodium channel isoforms during HF have shown varied results, most likely because of variations in species (rat, rabbit, dog) and HF model (pressure and/or volume overload and embolizations) used, with the most consistent observation comprising an upregulation of Na V 1.1 5, 23, 33. However, we observed unaltered I Na gating properties at the LM of failing myocytes in addition to unchanged single‐channel conductance in both the crest and groove/T‐tubule microdomains, arguing against a change in neuronal sodium channel function.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the cardiac sodium channel Na V 1.5, neuronal sodium channel isoforms (ie, Na V 1.1, Na V 1.3, and Na V 1.6) are also thought to populate the T tubules 29, 30, 31, 32. Studies on expression and function of neuronal sodium channel isoforms during HF have shown varied results, most likely because of variations in species (rat, rabbit, dog) and HF model (pressure and/or volume overload and embolizations) used, with the most consistent observation comprising an upregulation of Na V 1.1 5, 23, 33. However, we observed unaltered I Na gating properties at the LM of failing myocytes in addition to unchanged single‐channel conductance in both the crest and groove/T‐tubule microdomains, arguing against a change in neuronal sodium channel function.…”
Section: Discussionmentioning
confidence: 99%
“…Although NaV1.5 underlies the majority of I Na , other “non-cardiac” isoforms may make up an important part of cardiac I Na . In particular, the nerve/brain isoforms NaV1.1 [20] and NaV1.8 [21] may underlie an important part of late I Na in human heart. Other components of the complex that may play important roles in regulating late I Na in human heart include α1-syntrophin (Snta1) [22], caveolin 3 (Cav3) [23], and calmodulin kinase 2(CaMKII) [24].…”
Section: Sodium Channel Macromolecular Complexmentioning
confidence: 99%
“…The sustained sodium current is thought to be produced, in large part, by Nav1.5 channels that reopen during the prolonged depolarization of the cardiac action potential plateau (Antzelevitch et al, 2014). It was recently proposed that sodium channel pore-forming subunits other than the SCN5A subunit can also contribute to this current (Biet et al, 2012; Mishra et al, 2015). In particular, about 44% of I Na,late in the canine ventricles is highly TTX sensitive and therefore can be ascribed to sodium channels other than SCN5A (Biet et al, 2012).…”
Section: Transmural Gradient In Ina Densitymentioning
confidence: 99%
“…In particular, about 44% of I Na,late in the canine ventricles is highly TTX sensitive and therefore can be ascribed to sodium channels other than SCN5A (Biet et al, 2012). These non-SCN5A channels also contribute to alterations in I Na,late expression in a canine model of heart failure (Mishra et al, 2015). …”
Section: Transmural Gradient In Ina Densitymentioning
confidence: 99%